Burden of Teenage Pregnancies in Hilly Area of Eastern Region of Nepal (Journal of Nobel Medical College, 2015)
Teenage pregnancy, which is detrimental to the health of mother and child, is a common public health problem worldwide. It is a problem that affects nearly every society- developed and developing alike. The objective of this study was to find out the prevalence of teenage pregnancy and its impact on birth outcome. The cross-sectional study was conducted among the residents of Dhankuta municipality where 246 households were taken as subjects. Chi-square test was applied to find out the significant difference between socio demographic characteristics and outcome variable i.e. birth outcome & age of 1st pregnancy. About 34.6% of respondents were pregnant at below 20 years of age. The teenage pregnancies decreases as education level increases (p